'*Why you can't ask a proper question?' – The Learning Difficulties of Hong Kong ESL Students. (December 2016) - Lee, Jackie F.K.
Despite the high frequency of occurrences of wh -interrogatives in daily use, there are repeated negative comments about the poor mastery of the wh -interrogative structure among Hong Kong students. However, so far little attention has been paid to their difficulties in the acquisition of the structure. There is a strong need to understand what linguistic knowledge they possess, and identify the learning difficulties in order to seek ways to address them. This study obtained its quantitative data from three classes of Hong Kong Secondary 3 students through a written test and an oral test. The major learning difficulties found include the word order transfer from the Chinese language, failure to use correct verb phrase structures, and erroneous use of some wh -words ( whose, which, and how ) and wh -phrases (e.g. how far, whose bag ). The findings also reveal learning difficulties related to learner variables. Students of different English proficiency levels showed wide variation in their understanding of interrogative structures. The pedagogical implications are discussed.